Healthcare practitioner behaviours that influence unsafe use of hospital information systems - Salahuddin L.; Ismail Z.; Hashim U.R.; Ismail N.H.; Raja Ikram R.R.; Abdul Rahim F.; Hassan N.H. (SAGE Publications Ltd, 2023)
adult; article; drug safety; government; health care personnel; hospital information system; human; medical information system; patient care; patient safety; qualitative analysis; qualitative research; semi structured interview; patient safety; physician; public hospital; Hospital Information Systems; Hospitals, Public; Humans; Patient Safety; Physicians; Qualitative Research